2017
DOI: 10.15252/emmm.201707882
|View full text |Cite
|
Sign up to set email alerts
|

Household triclosan and triclocarban effects on the infant and maternal microbiome

Abstract: In 2016, the US Food and Drug Administration banned the use of specific microbicides in some household and personal wash products due to concerns that these chemicals might induce antibiotic resistance or disrupt human microbial communities. Triclosan and triclocarban (referred to as TCs) are the most common antimicrobials in household and personal care products, but the extent to which TC exposure perturbs microbial communities in humans, particularly during infant development, was unknown. We conducted a ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 42 publications
(44 reference statements)
2
52
0
Order By: Relevance
“…We previously showed the effectiveness and safety of omalizumab in children with severe allergic asthma. 1,2 However, data on optimal treatment duration and discontinuation are limited. 3 They mainly concern adults.…”
Section: Conf Licts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed the effectiveness and safety of omalizumab in children with severe allergic asthma. 1,2 However, data on optimal treatment duration and discontinuation are limited. 3 They mainly concern adults.…”
Section: Conf Licts Of Interestmentioning
confidence: 99%
“…and it has been detected in various human tissues and fluids. 1,2 In addition, toxicological studies have shown that TCS exposure induces physiological perturbations in animals and in humans. 4,5 Recently, a risk assessment undertaken by the US Food and Drug Administration (FDA) revealed that TCS was present in the urine samples of 75% of the US general population, and, in 2016, the FDA banned its use in soap products.…”
mentioning
confidence: 99%
“…In addition to vertical modes of transmission, the infant GIM may be continuously modified by environmental exposures; for example, maternal and/or infant antibiotic exposure is associated with a reduction in overall taxonomic richness and diversity of the infant GIM (Nogacka et al, ; Yasmin et al, ). Additionally, GIM composition may be influenced by pet ownership and proximity to animals (Azad et al, ; Tun et al, ), parental sanitation practices (pacifier cleaning method: Hesselmar et al, ; use of specific household products: Ribado et al, ) and other environmental factors varying by geographic location (Grześkowiak et al, ; Lin et al, ; Stearns et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…92 For example, antimicrobial resistance may simply be facilitated in ecosystems with higher microbial biomass and activity than the skin, as well as access to nutrients and moisture, such as the digestive tract or waste water systems. 95,96 Resistance may also be facilitated in areas with more consistent presence of antimicrobials such as building products, 46,47 which may be imbued with chemicals during manufacturing or may accrue chemicals from cleaning or hygiene produce residues. Mammalian host tissues readily absorb TCS, but sequester it in areas of the body apart from the host's microbial communities.…”
Section: Resistance and Sustainabilitymentioning
confidence: 99%